Clinical reasoning development in medical students: an educational transcultural comparative study - Silva, Ana L. (2013)
Clinical reasoning research has concluded that experts use less, but more selective, knowledge in a more efficient way, based on the construction of schema, scripts and other representations of the relation between signs, symptoms and diagnoses, derived from their experience. However, this conclusion does not help Medical Schools to decide which pedagogical strategies should be adopted to foster clinical reasoning in undergraduates. This study aims to investigate how medical students, approach clinical cases and the impact of three types of curriculum upon their clinical reasoning.